2015
DOI: 10.1109/mcse.2015.86
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Citizen Science Volunteers' Behaviors with Data from Usage Logs

Abstract: Web-based citizen science projects collect logs of interactions between volunteers and project websites. Visualization techniques can help infer volunteer behavior in such projects, perhaps shedding light on why people join or leave them. Better understanding of these factors could help citizen science project developers recruit and retain their volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…LA have been used less frequently to understand participation and learning in informal learning settings ( Ferguson et al 2016 ). Such studies have examined learning at the workplace (e.g., Littlejohn 2017 ), interactions in technology-mediated social systems such as online forums (e.g., Kloetzer, Schneider, and Costa 2016 ), and a few CS projects examining adult participation ( Aristeidou et al 2017 ; Dittus, Quattrone, and Capra 2016 ; Morais, Santos, and Raddick 2015 ; Ponciano and Brasileiro 2014 ). In this paper, we use LA as a methodology that allows a fine-grained analysis of young people’s participation (aged 5−19) in Zooniverse projects as a first step towards understanding and improving their learning experiences in online CS.…”
Section: Background Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…LA have been used less frequently to understand participation and learning in informal learning settings ( Ferguson et al 2016 ). Such studies have examined learning at the workplace (e.g., Littlejohn 2017 ), interactions in technology-mediated social systems such as online forums (e.g., Kloetzer, Schneider, and Costa 2016 ), and a few CS projects examining adult participation ( Aristeidou et al 2017 ; Dittus, Quattrone, and Capra 2016 ; Morais, Santos, and Raddick 2015 ; Ponciano and Brasileiro 2014 ). In this paper, we use LA as a methodology that allows a fine-grained analysis of young people’s participation (aged 5−19) in Zooniverse projects as a first step towards understanding and improving their learning experiences in online CS.…”
Section: Background Literaturementioning
confidence: 99%
“…Their metrics (adopted also in this study) capture time potentially linked to a project, days actually linked to a project, active days, time devoted to tasks per day, and elapsed time between two active days. Morais, Santos, and Raddick (2015) highlighted the evolution in number of volunteers and classifications over time and showed that the majority of classifications in Zooniverse were completed in the first 600 days of the project, and sharply declined afterwards. They also explained “bursts” of activity and analysed volunteers joining or leaving a project in short intervals.…”
Section: Background Literaturementioning
confidence: 99%
“…At the same time, they have the opportunity to learn and generate knowledge (Franzoni & Sauermann, 2014), to enhance their scientific literacy and to enjoy the experience (Bonney et al, 2009;Cronje, Rohlinger, Crall, & Newman, 2011). For professional scientists, the participation of a large number of contributors potentially helps expedite research projects (Haklay, 2013;Morais, Santos, & Raddick, 2015) and reduce their overall cost (Nov, Arazy, & Anderson, 2014). In addition to benefits for researchers and citizens, citizen science represents a potential means to raise social innovation by addressing problems of social interest through new aggregations of collaborating individuals (Cappa, Facci, & Ubertini, 2015;Mulgan, 2006;Murray, Caulier-Grice, & Mulgan, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, to keep citizen scientists engaged with my research I constantly moderated the discussion forums of the website and provided regular feedback and research updates. Understanding the motivations, expertise and demographics of the target audience can facilitate project managers to identify the most efficient method to keep citizen scientists engaged (Morais et al 2015). In summary, iterative periods of design, evaluation, and revision are crucial to ensure citizen scientists achieve the project-specific education and research goals (Dickinson et al 2012).…”
Section: Citizen Sciencementioning
confidence: 99%
“…For example, understanding the characteristics of the citizen scientists can facilitate the most efficient approach to provide feedback and research updates to the volunteers (i.e. crucial processes to achieve and maintain sustainable engagement of citizen scientists) (Morais et al 2015). To prevent and filter poor quality data, researchers can train citizen scientists, design the project to produce spatial and temporal replications or weight the information collected by citizen scientists based on user-specific accuracy (Isaac et al 2014;Kosmala et al 2016).…”
Section: Introduction Citizen Sciencementioning
confidence: 99%